2007
DOI: 10.1038/sj.npp.1301602
|View full text |Cite
|
Sign up to set email alerts
|

Supply of a Nondrug Substitute Reduces Escalated Heroin Consumption

Abstract: Escalation of drug consumptionFa hallmark of addictionFhas been hypothesized to be associated with a relative devaluation of alternative nondrug rewards and thus with a decrease in their ability to compete with or to substitute for the drug. In a behavioral economic framework, decreased substitutability of nondrug rewards for drug would explain why drug consumption is behaviorally dominant and relatively resistant to change (eg price-inelastic) in drug-addicted individuals. The goal of the present study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 70 publications
6
82
0
Order By: Relevance
“…In general, it appears that all natural rewards can be protective. Drug self-administration is reduced by the availability of a sweet such as saccharin or a glucose + saccharin mixture [83][84][85]. Drug self-administration is reduced by the availability of a running wheel, particularly in females [86].…”
Section: The Model: Drug Self-administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it appears that all natural rewards can be protective. Drug self-administration is reduced by the availability of a sweet such as saccharin or a glucose + saccharin mixture [83][84][85]. Drug self-administration is reduced by the availability of a running wheel, particularly in females [86].…”
Section: The Model: Drug Self-administrationmentioning
confidence: 99%
“…Environmental enrichment also is protective in rats when provided during adulthood alone [90]. Sweets and even chow are protective when presented in adulthood concurrent with the opportunity to self-administer drug [83][84][85]. Finally, the sweets need not be concurrently available to be protective in adult rats.…”
Section: The Model: Drug Self-administrationmentioning
confidence: 99%
“…Consistent with the notion that escalation of drug intake is an important step in the development of compulsive drug use, it has been shown that, after escalated cocaine or alcohol self-administration, other behavioral characteristics of addictive behavior can also be observed. These include increased motivation for the drug (Paterson and Markou, 2003;Liu et al, 2005;Lenoir and Ahmed, 2008;Wee et al, 2008;Orio et al, 2009), increased sensitivity for reinstatement of drug seeking after extinction (Mantsch et al, 2004;Ahmed and Cador, 2006;Kippin et al, 2006;Knackstedt and Kalivas, 2007) and reduced sensitivity to punishment (Wolffgramm, 1991;Wolffgramm andHeyne, 1991, 1995;H ö lter et al, 1998;Spanagel and H ö lter, 1999;Vanderschuren and Everitt, 2004;Lesscher et al, 2010;Ahmed, 2012).…”
Section: Escalation Of Drug Usementioning
confidence: 99%
“…As illustrated in figure 1C [35], the daily number of infusions that are self-administered by animals given short-access (i.e., 1 hour; ShA) to cocaine remained stable over 12 days (filled circles); whereas, when given long access (i.e., 6 hours) to cocaine the daily number of self-administered infusions drastically increased over 12 days (open circles). The observation of escalated rates of drug-intake after long-access training is a highly replicable phenomenon that has been documented to occur for several drugs of abuse including cocaine [35], methamphetamine [37] and heroin [38]. Many different laboratories are beginning to use this long-access training procedure in order to study the neurobiological [39,40,41] and behavioral [42,43] consequences of a history of escalated cocaine intake.…”
Section: Long-access Training and Intake Escalationmentioning
confidence: 99%